2012
DOI: 10.1371/journal.pone.0047427
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Oxidative Stress Causes Chlamydial Persistence during Non-Productive Human Herpes Virus Co-Infection

Abstract: Both human herpes viruses and Chlamydia are highly prevalent in the human population and are detected together in different human disorders. Here, we demonstrate that co-infection with human herpes virus 6 (HHV6) interferes with the developmental cycle of C. trachomatis and induces persistence. Induction of chlamydial persistence by HHV6 is independent of productive virus infection, but requires the interaction and uptake of the virus by the host cell. On the other hand, viral uptake is strongly promoted under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 57 publications
5
60
0
Order By: Relevance
“…In contradiction, other reports have shown that HHV6 infection upregulates the levels of pro-inflammatory cytokines, such as IL-1β, TNFα, and IFNγ in peripheral blood mononuclear cells [89,90]. The latter effects may well explain why HHV6 infections are associated with dramatically elevated cellular levels of oxidative stress [91]. A combination of elevated inflammatory cytokines and oxidative stress induces mitochondrial dysfunction [29].…”
Section: Human Herpes Virusmentioning
confidence: 90%
“…In contradiction, other reports have shown that HHV6 infection upregulates the levels of pro-inflammatory cytokines, such as IL-1β, TNFα, and IFNγ in peripheral blood mononuclear cells [89,90]. The latter effects may well explain why HHV6 infections are associated with dramatically elevated cellular levels of oxidative stress [91]. A combination of elevated inflammatory cytokines and oxidative stress induces mitochondrial dysfunction [29].…”
Section: Human Herpes Virusmentioning
confidence: 90%
“…HeLa cells containing latent HHV-6, HSB-2 and Molt-3 cells [23] were grown in RPMI 1640 media and 5% fetal bovine serum (FBS) at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Although C. trachomatis and C. pneumoniae differ in their tissue tropism, they have a similar infection physiology. In a previous study, we have shown that co-infection with HHV-6 influences the development of infectious progeny of both, C. trachomatis and C. pneumoniae [23]. Moreover, different herpes viruses like herpes simplex virus (HSV)-1 and HSV-2 and human cytomegalovirus influence chlamydial infectivity in a similar way [23].…”
Section: Introductionmentioning
confidence: 99%
“…P53 is known to inhibit the PPP which is important for the production of NADPH and nucleotide precursors (Jiang et al 2011). All Chlamydia depend on the host cell pool of NADPH (Prusty et al 2012) and nucleotide precursors and therefore p53-mediated shutdown of the PPP results in block of bacterial growth (Siegl et al 2014). Glucose-6-phosphate dehydrogenase (G6PD) is the first enzyme in the PPP and the major target of p53.…”
Section: Depletion Of P53mentioning
confidence: 99%